Clinical Characteristics of Bangladeshi COVID-19 patients During First Hospital Reporting (Anwer Khan Modern Medical College Journal, 2020)
Background: Covid-19 is a new disease first originated in Wuhan, China in December 2019. It is now pandemic globally1, 2. The disease affected almost all countries of the world.Aims and objectives: To see different aspects of clinical presentations of COVID-19 in Bangladesh.Methods: Subjects tested, admitted and treated were included in the study. Total 441 cases were included for the study. Data was collected, compiled and analyzed.Results: Male: female ratio, n= 441, Ratio= 2.4:1. Nasopharyngeal swab was positive in 59% and 41% oropharyngeal sample was positive. 74% test was positive among 220 patients and 26% negative. Smoking accounts for 65% among predisposing factors. Among the co-morbid conditions Hypertension accounts for 37%, Bronchial asthma 23%, Diabetes mellitus 30%. Clinical symptoms were fever 90%, body ache 95%, cough 80%, and headache were 75%. Other symptoms were less. Symptoms may one or more in the same patient. In our series 30 (07%) cases were had respiratory distress. All of them needed hospital admission. 27 of them were cured by oxygen and medications.Nine patients were trans- ferred to ICU, where they succumbed to death 2%.Conclusion: In this COVID-19 pandemic no symptom should be neglected. Prompt consultation, appropriate test and early, adequate and aggressive treatment should be instituted according to severity.AKMMC J 2020; 11(2) : 120-123